Sosialisasi Tentang Literasi Media Dalam Mengantisipasi Penyebaran Informasi - Sitorus, Amalia Azmi; Rakhmayanti, Risda; Puspitasari, Siska (Jurnal Media Pengabdian Komunikasi, 2023)
Abstract Social media is a new innovation in communication patterns which were initially one-way, namely from one source to another, then changed to being from several sources to several other sources. The crucial issue that is currently troubling in the digital era is the increasing prevalence of hoax information. Digital Literacy is the ability to search for information so that the information obtained is more accurate and when teenagers grow up they can be better directed. Digital literacy is not only limited to being able to use media, but rather the ability to analyze, disseminate or assess the information obtained. The purpose of this service is to explain the importance of media literacy in the problem of deliberately created hoaxes. The method used is through delivery of material and discussion. The result of this service is an increase in understanding of the importance of media literacy, so that students become more knowledgeable in selecting and disseminating information that is inversely proportional to existing facts, generating opinions, forming perceptions and testing the accuracy and intelligence of internet and social media users in reading. and receive information. The consequences resulting from the spread of hoax news itself are misunderstandings, misunderstandings, and even divisions between elements of society. Moreover, the younger generation has become active users on social media, creating vulnerability in the spread of hoax information. For this reason, it is necessary to provide information about media literacy to minimize hoaxes among young people who are students of SMA PGRI 3 Jakarta. Keywords: Digital; information; literacy; media.Abstrak Media sosial merupakan suatu inovasi baru dalam pola komunikasi yang pada awalnya bersifat satu arah yaitu dari satu sumber kepada sumber lain, kemudian berubah menjadi dari beberapa sumber kepada beberapa sumber lain. Persoalan krusial yang meresahkan saat ini di era digital adalah semakin marak informasi hoaks. Literasi Digital merupakan kemampuan dalam pencarian informasi menjadikan informasi yang didapat lebih akurat dan ketika remaja beranjak dewasa dapat diarahkan dengan lebih baik. Literasi digital tidak hanya sebatas dapat menggunakan media, tetapi lebih pada kemampuan menganalisis, mengevaluasi atau menilai informasi yang didapat. Tujuan pengabdian ini untuk menjelaskan tentang pentingnya literasi media pada masalah hoax yang dibuat secara sengaja. Metode yang digunakan melalui penyampaian materi dan diskusi. Hasil dari pengabdian ini adalah adanya peningkatan pemahaman tentang pentingnya literasi media, sehingga siswa-siswi menjadi paham teruata dalam memilih dan menyebarkan informasi yang berbanding terbalik dengan fakta yang ada, menggiring opini, membentuk persepsi serta menguji kecermatan serta kecerdasan pengguna internet dan media sosial dalam membaca serta menerima informasi. Akibat yang ditimbulkan dari penyebaran berita hoax itu sendiri adalah keributan, kesalahpahaman, hingga perpecahan antar elemen masyarakat. Terlebih generasi muda yang menjadi pengguna aktif di media sosial sehingga menimbulkan kerentanan dalam penyebaran informasi hoax. Untuk itu perlu dilakukan sosialisasi tentang literasi media untuk meminimalisir hoax kepada kaum muda yang merupakan siswa/siswi SMA PGRI 3 Jakarta. Kata-kata kunci:  Digital; informasi; literasi; media.